2005
DOI: 10.1248/bpb.28.2319
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Activity of Alcoholic Extract of Tinospora cordifolia in Ischemia-Reperfusion Induced Myocardial Infarction in Rats

Abstract: It has been suggested that the beneficial effects of reperfusing the myocardium might be in part reversed by the occurrence of reperfusion injury. Oxidative stress was suggested to be implicating in the pathogenesis of ischemia-reperfusion (I/R) injury. Many antioxidative plants were shown to be cardioprotective in experimental models of myocardial ischemia-reperfusion (I/R) injury. The present study was designed to investigate the effects of pretreatment with alcoholic extract of Tinospora cordifolia in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 29 publications
(18 reference statements)
7
78
0
2
Order By: Relevance
“…2,3,18,19,41 The discrepant effect on oxidative stress suggests that heme-catalyzed reactive species generation may differ from reactive species generated in other experimental conditions. Alternatively, silymarin-induced p53 activation could upregulate genes that encode ROS-generating enzymes (PIG 3, PIG 6) 42 or suppress antioxidant genes (MnSOD), 43 either way tipping the balance toward oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,18,19,41 The discrepant effect on oxidative stress suggests that heme-catalyzed reactive species generation may differ from reactive species generated in other experimental conditions. Alternatively, silymarin-induced p53 activation could upregulate genes that encode ROS-generating enzymes (PIG 3, PIG 6) 42 or suppress antioxidant genes (MnSOD), 43 either way tipping the balance toward oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…SD rats were randomly divided into 3 groups, as follows: i) Control group rats (n=10), administered saline solution; ii) I/R group rats (n=10), receiving the aforementioned lung I/R injury and administered saline solution; iii) silymarin group rats (n=10), receiving lung I/R injury and administered 250 mg/kg/day of silymarin (Sigma-Aldrich, St. Louis, MO, USA) for 8 days (8).…”
Section: Methodsmentioning
confidence: 99%
“…Rao and Viswanath 2007 [19] reported that the administration of SM before ischemia-reperfusion-induced myocardial infarction maintained the levels of marker enzymes (LDH, CK and CK-MB) compared to isoproterenol-injected rats. A possible explanation is that silymarin, via its anti-lipid peroxidation activity, causes stabilization of cardiac membranes and prevents the leakage of cardiac enzymes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin has cardioprotective activity against ischemia-reperfusion induced myocardial infarction in rats [19].…”
Section: Introductionmentioning
confidence: 99%